2020
DOI: 10.1002/cpsc.108
|View full text |Cite
|
Sign up to set email alerts
|

Generation and Functional Characterization of Monocytes and Macrophages Derived from Human Induced Pluripotent Stem Cells

Abstract: Monocytes and macrophages are essential for immune defense and tissue hemostasis. They are also the underlying trigger of many diseases. The availability of robust and short protocols to induce monocytes and macrophages from human induced pluripotent stem cells (hiPSCs) will benefit many applications of immune cells in biomedical research. Here, we describe a protocol to derive and functionally characterize these cells. Large numbers of hiPSC‐derived monocytes (hiPSC‐mono) could be generated in just 15 days. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 31 publications
1
17
0
Order By: Relevance
“…This is an increase in yield of 4.3x per cm 2 culture surface and has significant cost savings (1000USD per run) of expensive growth factors and cytokines. The new protocol produces 2.5-4 x10 6 CD14+ monocytes per harvest and up to 3.5 x10 7 cells over the course of a single differentiation run which compares very well to other recently published methods [21,22].…”
Section: Induced Pluripotent Stem Cell Derived Macrophages and Dendrisupporting
confidence: 65%
“…This is an increase in yield of 4.3x per cm 2 culture surface and has significant cost savings (1000USD per run) of expensive growth factors and cytokines. The new protocol produces 2.5-4 x10 6 CD14+ monocytes per harvest and up to 3.5 x10 7 cells over the course of a single differentiation run which compares very well to other recently published methods [21,22].…”
Section: Induced Pluripotent Stem Cell Derived Macrophages and Dendrisupporting
confidence: 65%
“…Cryopreservation of intermediate stages, in this case macrophage progenitors, would be highly desirable. While others reported progress in this area [ 49 ], we have not managed to cryopreserve cells with good recovery rates, which will be a point to further address and optimize in the near future. However, by introducing and characterizing the prolonged cultivation of macrophage progenitors in suspension culture, we were able to overcome this limitation by various means.…”
Section: Discussionmentioning
confidence: 99%
“…We managed a robust culture of myeloid factories in culture vessels with up to 1000 cm 2 , resulting in 20–60 million macrophage progenitors per harvest. Recently published work of others also aimed at increasing the yield or at decreasing the differentiation time of similar protocols [ 19 , 49 ]. It was shown that the myeloid factory state can be transferred to stirring cultures, which could be run in industry compatible bioreactors to generate sufficient cells for cell therapy approaches [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations